An exploratory landscape metrics approach for agricultural sustainability - Vaz, Eric (2013)
Socio-economic growth and urban change have been an increasing concern for decision makers in recent decades. Led by the creation of new infrastructures to support economic activity, periurban areas have mostly become adversely affected and the consequences for the ecological but also the rural landscape have become a lasting concern. The monitoring and mapping of land-use change, especially in areas where urban change has been high, is crucial. The collision between traditional economic activities related to agriculture in tourist areas such as the Algarve and current demand for tourism infrastructures in urban regions is also leading to loss of economic activity. This paper uses a combined Geographical Information System approach with remotesensing imagery and land cover databases to perform a Markov analysis for the purpose of quantifying changes in agricultural areas. The paper then expands on the nature of the agricultural changes observed, and offers a multi-temporal assessment by means of landscape metrics in order to understand the shifting land-use patterns for the Algarve in land use planning and regional economic equilibrium: (1) forest regions become transformed into agricultural areas and agricultural areas become urban; (2) areas which are initially agricultural become scattered residential regions created by economic investors; and (3) changes in the land-use have a cyclical nature in which in the course of the economic recession we may witness a shift in this effect brought about a decrease in tourism and focus on traditional sectors.